(untitled) (Balthazar, 2021)
Variations sur des thèmes communs is the editorial of the first number of “Questions feminists”, published from 1977 to 1980, under the direction of Simone de Beauvoir. The purpose of the group of women that founded the journal was to analyse the social condition of women and their grouping in a sex social class with the instrument of a feminism that they defined “radical and materialist”. The radicality of their approach consisted in the investigation of the root causes of social inequality between the two sexes, attacking and distancing themselves from naturalistic evidences about sexual difference. The latter is here recognized as social and historical, and only at a later time justified by patriarchal discourse through anatomical differences. If subordination is established and expressed in this ideological apparatus too, it is first and foremost to the materiality of domestic work that women carry out for free and to the control, which is also sexual, of female bodies that one must turn to dismantle it. The theory of history that makes such analysis possible is genuinely materialist, as sociologist Christine Delphy explains: the ways in which life is materially produced and reproduced is at the foundation of the organization of every society, both at individual and collective level, and history can be interpreted as the domination of certain social groups on the others. It is an approach that wants to bring together the theoretical and the political aspects of the question: the aim of theoretical analysis is practical action, in order to modify social reality towards a non-hierarchical society. We propose today the Italian translation of this text because, thanks to its steadfast militant political aspiration and to its equally steadfast critical clarity, it still seems very relevant to the members of the editorial board. For the same reasons, we decided to place it in the “Essays” section: we believe that, even after more than forty years, the reflections developed in this text can dialogue in a profitable way with the more recent perspectives expressed in the other articles of this number of Balthazar, offering essential tools to unmask the logics of domination and control that are still operative and the tendency to appeal to various forms of essentialism that can only give rise to new powerful oppressions.